Platinumdiaminopropane dichloride - M.P.M. Marques, University of Coimbra, Portugal (My University, 2012)
Inelastic Neutron Scattering spectrum of Platinumdiaminopropane dichloride, Pt(dap)Cl₂, measured on the TOSCA instrument.
Keywords: TOSCA